2020
DOI: 10.1161/strokeaha.119.026589
|View full text |Cite
|
Sign up to set email alerts
|

Intravenously Transplanted Human Multilineage-Differentiating Stress-Enduring Cells Afford Brain Repair in a Mouse Lacunar Stroke Model

Abstract: Background and Purpose— Multilineage-differentiating stress-enduring cells are endogenous nontumorigenic reparative pluripotent-like stem cells found in bone marrow, peripheral blood, and connective tissues. Topically administered human multilineage-differentiating stress-enduring cells into rat/mouse stroke models differentiated into neural cells and promoted clinically relevant functional recovery. However, critical questions on the appropriate timing and dose, and safety of the less invasive int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…1 a,b). It was also reported that IV-injected Muse cells clearly showed a therapeutic effect in functional recovery of the acute stroke mice model, in a dose-dependent manner 24 . IV-administration has greater advantages over IT-administration because of easy accessibility, less-invasiveness and less-burden for patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…1 a,b). It was also reported that IV-injected Muse cells clearly showed a therapeutic effect in functional recovery of the acute stroke mice model, in a dose-dependent manner 24 . IV-administration has greater advantages over IT-administration because of easy accessibility, less-invasiveness and less-burden for patients.…”
Section: Discussionmentioning
confidence: 92%
“…For ex-vivo dynamics of IV-injection, vehicle (HBSS), Nano-lantern-labeled-MSCs and -Muse cells (1.0 × 10 5 cells/250 μl) were intravenously injected when mice were 14 weeks old. After 7 days, animals were sacrificed under deep anesthesia and analyzed as described previously 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When injected near the postinfarct area in a mouse lacunar stroke model, ∼34% of topically injected human PB-SSEA-3(+) cells expressed the neuronal marker NeuN at 7 d after administration. Similarly, in a mouse lacunar stroke model, locally and intravenously injected human BM- and dermal-Muse cells integrate into the postinfarct tissue and spontaneously differentiate into cells positive for several neuronal markers, including NeuN, at 7 d after administration 12 , 13 , 23 . In the damaged muscle tissue, locally injected human PB-SSEA-3(+) cells expressed satellite cell marker Pax7 and muscle cell marker desmin at 7 d, similar to the spontaneous differentiation of intravenously injected human BM-Muse cells in the mouse muscle degeneration model 3 .…”
Section: Discussionmentioning
confidence: 99%
“…As in the case with preclinical studies using HIE models, IV administration in rodent lacunar stroke models have shown donor cell migration, differentiation, and engraftment to the peri-infarct area as well as long-term functional recovery. [ 31 ] Clinical trials using IV donor-derived Muse cells (called CL2020 in the clinic) are ongoing for the treatment of myocardial infarction, stroke, and epidermolysis bullosa. Because human Muse cells express human leukocyte antigen (HLA)-G, an inhibitory receptor relevant to immunomodulation in the placenta, allogenic Muse cells may survive in the host tissue long-term without immunosuppression.…”
Section: Preclinical Studiesmentioning
confidence: 99%